Systematic Pharmacology and GEO Database Mining Revealed the Therapeutic Mechanism of Xuefu Zhuyu Decoration for Atherosclerosis Cardiovascular Disease - Liang, Bin; Xiang, Yang; Zhang, Xiaokang; Wang, Chen; Jin, Bingyu; Zhao, Yue; Zheng, Fang (Frontiers in Cardiovascular Medicine, 2020)
Background: Xuefu Zhuyu decoration (XFZYD), as a traditional Chinese compound recipe, has been used to treat atherosclerosis cardiovascular disease (ASCVD) for thousands of years in China, but its effective compounds and underlying treatment molecular mechanism remains promiscuous, which severely limits its clinical application. Methods: The effective components and their targets of XFZYD were predicted and screened based on the Traditional Chinese Medicine System Pharmacology (TCMSP) database. The candidate therapeutic targets of ASCVD were screened by Pharmacogenomics Knowledgebase (PharmGKB) and Comparative Toxicogenomics Database (CTD). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses for target proteins were performed using the Database for Annotation, Visualization and Integrated Discovery (DAVID) database. Differentially expressed genes were identified using the GEO2R online tool. Molecular docking was performed by Schrodinger software. To assess the efficacy of the prediction, human umbilical vein endothelial cells (HUVECs) treated with the effective compound of XFZYD were used as the in vitro model. Results: A total of 108 effective compounds (including quercetin) and 137 candidate therapeutic targets were identified. Analyzing the relationships among effective compounds, candidate therapeutic targets, and signaling pathways, the therapy mechanisms of XFZYD were mainly reflected in the protection of vascular endothelium, anti-inflammatory, antioxidant stress, etc. Accordingly, we found the effective compound of XFZYD (quercetin) decreased intracellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) expressions and pro-inflammatory cytokines in HUVECs treated with lipopolysaccharide (LPS), and reduced the adhesion function of HUVECs with monocytes. The inhibitor of the predicted target protein (PTGS2) could further reduce the expressions of VCAM-1, ICAM-1, and TNF-α induced by LPS, and inhibit the adhesion function of HUVECs with monocytes, while PTGS2 agonists partially counteracted the protective effect of quercetin. Conclusions: In this study, the effective components and potential therapeutic targets of XFZYD for ASCVD treatment were explored from the perspective of systemic pharmacology. The effective component quercetin was verified to protect endothelial cells by reducing endothelial inflammatory response and impeding the attachment of monocytes against the predicted therapeutic target PTGS2.